Global monitoring report 2014/2015 : ending poverty and sharing prosperity - The World Bank (Washington DC : The World Bank, 2015)
The report details, for the first time, progress toward the WBG's twin goals of ending extreme poverty by 2030 and promoting shared prosperity and assesses the state of policies and institutions that are important for achieving them.
osc 24/10/17
Ref
Keywords: Poverty; Economic policy; Developing countries